Changes of Sublingual Microcirculation during the Treatment of Severe Diabetic Ketoacidosis - Krausova, Vlasta; Neumann, David; Skvor, Jaroslav; Dostal, Pavel (Journal of clinical medicine, 2024)
Introduction: Diabetic ketoacidosis (DKA) is associated with volume depletion and hemodynamic alterations. Changes in systemic microcirculation during DKA have not been described so far. Methods: In this case report, we describe the evolution of sublingual microcirculatory changes, monitored using sidestream dark field (SDF) imaging during the treatment of severe diabetic ketoacidosis in a 13-year-old girl. The patient presented a pH of 6.84, a glycemia level of 27.2 mmol/L, a ketonemia level of 5.6 mmol/L, a base excess of -29.4 mmol/L, hypernatremia, hyperosmolality due to acute gastritis, and a malfunction of the glucose sensor. Sublingual microcirculation measurements using an SDF probe were initiated 60 min after the initiation of treatment, which was then repeated 2, 3, 4, 6, 12, and 24 h after treatment initiation, as well as on the day of discharge. Results: Substantial alterations of microvascular perfusion parameters, both total and small vessel densities, perfused vessel densities, and the DeBacker score, were observed during the first 6 to 12 h of treatment. The degree of microcirculatory alteration was strongly negatively correlated with calculated osmolality, sodium levels, ketone and lactate levels, and blood pressure values. Conclusions: DKA is, in its complexity, associated with a serious microcirculatory alteration. SDF imaging provides insight into the severity of the patient's microcirculatory alteration and its evolution during treatment.
Keywords: hypertension; diabetic ketoacidosis; sublingual microcirculation